Effects of Remote Immune Activation on Performance in the 5-Choice Serial Reaction Time Task Following Mild Traumatic Brain Injury in Adolescence - Kaukas, Lola; Krieg, Justin; Collins-Praino, Lyndsey; Corrigan, Frances (Frontiers in Behavioral Neuroscience, 2021)
In adult pre-clinical models, traumatic brain injury (TBI) has been shown to prime microglia, exaggerating the central inflammatory response to an acute immune challenge, worsening depressive-like behavior and enhancing cognitive deficits. Whether this phenomena exists following mTBI during adolescence has yet to be explored, with age at injury potentially altering the inflammatory response. Furthermore, to date, studies have predominantly examined hippocampal dependent learning domains, although pre-frontal cortex driven functions, including attention, motivation and impulsivity, are significantly affected by both adolescent TBI and acute inflammatory stimuli. As such, the current study examined the effects of a single acute peripheral dose of LPS (0.33mg/kg) given in adulthood following mTBI in mid-adolescence in male Sprague Dawley rats on performance in the 5-choice serial reaction time task (5-CSRTT). Only previously injured animals given LPS showed an increase in omissions and reward collection latency on the 5-CSRTT, with no effect noted in sham animals given LPS. This is suggestive of impaired motivation and a prolonged central inflammatory response to LPS administration in these animals. Indeed, morphological analysis of myeloid cells within the pre-frontal cortex, via IBA1 immunohistochemistry, found that injured animals administered LPS had an increase in complexity in IBA1+ve cells, an effect that was seen to a lesser extent in sham animals. These findings suggest that there may be ongoing alterations in the effects of acute inflammatory stimuli that are driven, in part by increased reactivity of microglial cells.